Maternal and neonatal outcomes of women with CHD in pregnancy - Muller, Elani (Department of Public Health and Family Medicine, 2024)
Introduction Although pregnancy is generally well tolerated in women with congenital heart disease (CHD), little is known about maternal and neonatal outcomes of these pregnancies in sub-Saharan Africa. This study aimed to describe the maternal and neonatal outcomes as stratified by cyanotic vs. acyanotic CHD, previous surgically repaired vs. unrepaired CHD, and between the different Modified World Health Organisation risk stratification (mWHO) classes. Methods A nested retrospective cohort study was conducted that included 83 women with CHD out of the 243 women with CVD enrolled to a Cape Town-based registry from patients seen at a tertiary referral healthcare centre by November 2015. This study analysed poor maternal and neonatal outcomes in women with CHD. Poor maternal outcome was defined as maternal death, antenatal hospitalisation, and/or perinatal ICU admission. Poor neonatal outcome was defined as preterm birth, low birth weight, NICU admission, general ward admission over 2 days, neonatal death, and/or miscarriage. Data were collected using REDCap, and statistical analyses included descriptive statistics, non-parametric tests, and logistic regressions to assess associations. Risk factors were adjusted for, and a two-tailed p-value <0.05 was considered significant. Results This cohort had a median age of 27 years (IQR 23 – 32) and gravidity of 2 (IQR 1 – 2). Women were enrolled with a median gestational age of 24 weeks (IQR 19 – 30). There were no statistically significant differences in clinical presentation at enrolment between those who had cyanotic CHD or not, and those who had surgically repaired CHD or not. More than half (54.2%) of women required either antenatal hospitalisation and/or perinatal intensive care unit (ICU) admission. Women classified as mWHO class II, II-III, III or IV were at increased risk of poor maternal outcome (OR 4.239, 95% CI 1.4 – 12.5), even when corrected for confounders. Neonates born from mothers from mWHO classes II-III, III and IV had an odds ratio of 3.1 (95% CI 1.8 – 8.2) for poor neonatal outcome but did not show significance when corrected for confounders. Univariable and multivariable regression analysis showed that the risk for poor neonatal outcome increased with maternal age. Conclusion As more women with CHD are reaching child-bearing age, risk stratification is imperative to ensure optimal care and favourable maternal and neonatal outcomes. We found the mWHO classification a useful tool to predict poor outcomes and recommend its use to tailor appropriate level of care for women with CHD in pregnancy.